(untitled) (PANGEEA, 2025)
Contemporary morphodynamics of Ampoi River Basin. The water catchment area of the Ampoi valley is situated at the meeting point of two geomorphological units. The Metaliferi Mountains and the Mures river and is the subject of a study on fluvial geomorphology. This type of approach is part of a branch of practical geography and it also is a new way of analyses in this field. The introductory considerations on contemporary morphodynamics study the present geomorphological proces from the Ampoi water catchment area as well as the quantitative analysis of the relief expressed by the geomorphometry and the hypsometry of the catchement area, by the energy and fragmentation on the relief, by geodeclivity,by the exposure of the of the mountain slopes ot by the rate of the global denudation at the water catchement area leve land are followed by an anslysis of the dynamics of the catchement area on a micro and macroscalar leve land of the dynamic of the water bed. This type of approach reflects the functionality of the water catchment area of the Ampoi valley, the size and the frequency of the geomorphological proces, the seasond character and the frequency of some proceses or phenomenon.